A Low-Overhead, Fully-Distributed, Guaranteed-Delivery Routing Algorithm for Faulty Network-on-Chips - Mohammad Fattah; Antti Airola; Rachata Ausavarungnirun; Nima Mirzaei; Pasi Liljeberg; Juha Plosila; Siamak Mohammadi; Tapio Pahikkala; Onur Mutlu; Hannu Tenhunen (United States, 2022)
This paper introduces a new, practical routing algorithm, Maze-routing, to tolerate faults in network-on-chips. The algorithm is the first to provide all of the following properties at the same time: 1) fully-distributed with no centralized component, 2) guaranteed delivery (it guarantees to deliver packets when a path exists between nodes, or otherwise indicate that destination is unreachable, while being deadlock and livelock free), 3) low area cost, 4) low reconfiguration overhead upon a fault. To achieve all these properties, we propose Maze-routing, a new variant of face routing in on-chip networks and make use of deflections in routing. Our evaluations show that Maze-routing has 16X less area overhead than other algorithms that provide guaranteed delivery. Our Maze-routing algorithm is also high performance: for example, when up to 5 links are broken, it provides 50% higher saturation throughput compared to the state-of-the-art.
NOCS '15 Proceedings of the 9th International Symposium on Networks-on-Chip